2020
DOI: 10.1029/2020gb006598
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Regional Carbon Cycle Responses to Seasonal Climate Anomalies Across the East‐West Divide of Temperate North America

Abstract: Across temperate North America, interannual variability (IAV) in gross primary production (GPP) and net ecosystem exchange (NEE) and their relationship with environmental drivers are poorly understood. Here, we examine IAV in GPP and NEE and their relationship to environmental drivers using two state-of-the-science flux products: NEE constrained by surface and space-based atmospheric CO 2 measurements over 2010-2015 and satellite up-scaled GPP from FluxSat over 2001-2017. We show that the arid western half of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 90 publications
(161 reference statements)
9
14
0
Order By: Relevance
“…Recent inversion efforts that incorporate satellite-based CO 2 observations support these estimates for temperate eastern North America, showing a statistically significant sink of similar magnitude (∼0.5 Pg C) over the period 2010-2018 (Liu, Baskaran, et al, 2020). These results are encouraging as we move toward combined surface-and satellite-based inversion approaches to improve spatially and temporally integrated constraints of net CO 2 exchange at regional and global scales, and advance regional-scale understanding of terrestrial CO 2 sinks (e.g., Byrne, Liu, Bloom, et al, 2020;Byrne, Liu, Lee, et al, 2020).…”
Section: Introductionsupporting
confidence: 61%
“…Recent inversion efforts that incorporate satellite-based CO 2 observations support these estimates for temperate eastern North America, showing a statistically significant sink of similar magnitude (∼0.5 Pg C) over the period 2010-2018 (Liu, Baskaran, et al, 2020). These results are encouraging as we move toward combined surface-and satellite-based inversion approaches to improve spatially and temporally integrated constraints of net CO 2 exchange at regional and global scales, and advance regional-scale understanding of terrestrial CO 2 sinks (e.g., Byrne, Liu, Bloom, et al, 2020;Byrne, Liu, Lee, et al, 2020).…”
Section: Introductionsupporting
confidence: 61%
“…Drier summer and fall conditions could result from higher evapotranspiration in the spring, or also from increased early runoff due to earlier snowmelt during warm springs (Buermann et al, 2013). The ability of CESM2 to replicate the redistribution of NEP and GPP fluxes (Figures 4 and 8; Byrne et al, 2020) suggests that the representation of plant phenology and water stress in CESM2 are likely responding in physically and ecologically realistic ways to simulated climate variability. With seasonal redistribution, potential increases in plant productivity from an early green-up that were facilitated by warmer spring temperatures are negated by soil moisture stress later in the growing season, leading to negligible changes in the annual rates of gross and net carbon uptake (mean θ values close to zero for the redistribution vector; Figures 5 and 6).…”
Section: Seasonal Variabilitymentioning
confidence: 99%
“…Notably, Butterfield et al (2020) found that while local to regional-scale IAV in productivity was poorly correlated among remote sensing products (between 2007 and 2015), they could identify seasonal modes of variability that shared common features and environmental sensitivities. These included the (a) Amplification of the seasonal cycle of GPP, which was associated with increases in summertime soil moisture availability and positive anomalies in GPP, and (b) Seasonal redistribution of GPP that was initially driven by warmer springtime temperatures-resulting in positive GPP anomalies-but that was followed by higher-than-average soil moisture stress in the summer and fall-resulting in negative GPP anomalies (see also Byrne et al, 2020). Integrated over the growing season, the second mode of variability reflects climate driven shifts in the seasonal timing of photosynthesis, which has negligible changes in the annual C flux.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ecosystem responses are sensitive to the specific characteristics of the event, such as the intensity and timing (Bastos et al, 2014;De Boeck et al, 2011;Denton et al, 2017;Frank et al, 2015), legacy effects from previous disturbances (Bowd et al, 2021;Longo et al, 2020) and vegetation type (Turner et al, 2020;Zhang et al, 2016). The recent expansions of space-based observing systems of carbon-cycle-relevant quantities are now providing the opportunity for finer scale quantification of carbon cycle perturbations and more detailed understanding of the response of ecosystems to extreme drought, heat, and fire (Byrne, Liu, Lee, et al, 2020;Byrne, Liu, Bloom, et al, 2020;Byrne et al, 2019;Turner et al, 2020;Yin, Bloom, et al, 2020). In this study, we utilize space-based We combine observations from multiple satellites to quantify the carbon cycle anomalies within southeast Australia.…”
mentioning
confidence: 99%